2022
DOI: 10.1021/acssuschemeng.1c07459
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Reaction of Ethanol to Butadiene over Multifunctional Silica-Supported Ag and ZrO2 Catalysts

Abstract: Although butadiene is currently a byproduct of naphtha cracking, interest in producing butadiene from biobased ethanol has increased because of the lower environmental impact of the ethanol to butadiene reaction. This work explores a multifunctional catalyst system composed of silica-supported Ag and ZrO2 used for the cascade reaction of ethanol to butadiene at 573 K. The Ag and ZrO2 components were synthesized on separate support particles, enabling the characterization of each component without interference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…B and L acid signals appear at 1542 and 1476 cm −1 , respectively (Figure 5C); the B and L acid sites were determined to be present at 16.71 and 13.9 μmol/g, respectively, at 150°C (Table S3). The characteristic hydroxyl band is observed at 3661 cm −1 in the absence of pyridine adsorption, consistent with the adsorption of water molecules on the surface 47 (Figure 5D), which also provides a reason for the existence of the B acidic sites 48 …”
Section: Resultssupporting
confidence: 66%
“…B and L acid signals appear at 1542 and 1476 cm −1 , respectively (Figure 5C); the B and L acid sites were determined to be present at 16.71 and 13.9 μmol/g, respectively, at 150°C (Table S3). The characteristic hydroxyl band is observed at 3661 cm −1 in the absence of pyridine adsorption, consistent with the adsorption of water molecules on the surface 47 (Figure 5D), which also provides a reason for the existence of the B acidic sites 48 …”
Section: Resultssupporting
confidence: 66%
“…For example, 0.1 g of Ag-SiO 2 was physically mixed with 0.4 g of 2Y-SiO 2 while an analogous HBZ-based catalyst utilized a physical mixture of 0.1 g of Ag-SiO 2 with 0.05 g of 2Y-HBZ. To be consistent with our prior work, the mass ratio of Ag-SiO 2 to M-SiO 2 was chosen to be 1:4; however, this ratio was adjusted for M-HBZ samples as their relative activity was an order of magnitude greater than that of their silica analogues. c o n v e r s i o n false( C 0.25em % false) = 100 % · ( n i M i 2 M 0 ) selectivit y i 0.25em ( C % ) = 100 % · ( n i M i n i M i ) ST Y i = ( M i M m ) …”
Section: Methodsmentioning
confidence: 99%
“…Direct comparisons among Lewis acid cations and supports used in the valorization of ethanol to C 4 and C 4+ products have been limited because the co-impregnation of components such as Zn and/or Cu have been previously shown to exhibit Lewis acid character of their own when supported on β zeolite . Previously, our group has shown that a co-impregnated Ag-ZrO x -SiO 2 catalyst behaves similarly to that of a catalyst system composed of a physical mixture of Ag-SiO 2 and ZrO x -SiO 2 . The physical separation of Ag metal and ZrO x on different support particles allowed for a direct evaluation of performance of the different components without mutual interference.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a plentiful supply of inexpensive petroleum and the steam-cracking of naphtha developed in the 1960s, the research on converting ethanol to BDE fell out of favor. Converting bioethanol into BDE selectively over a multifunctional catalyst has received renewed interest in the 21st century . The resurgence of this research interest over the past decade is fuelled by the incentives in sustainable technologies, stricter environmental regulations, and inexpensive bioethanol from nonfood cellulosic and algal biomasses .…”
Section: 3-butadienementioning
confidence: 99%
“…Converting bioethanol into BDE selectively over a multifunctional catalyst has received renewed interest in the 21st century. 119 The resurgence of this research interest over the past decade is fuelled by the incentives in sustainable technologies, stricter environmental regulations, and inexpensive bioethanol from nonfood cellulosic and algal biomasses. 120 The mechanism of transforming ethanol into BDE involves the dehydrogenation of ethanol into acetaldehyde, which then undergoes an aldol reaction to form acetaldol.…”
Section: 3-butadienementioning
confidence: 99%